A responsabilidade do município decorrente do parcelamento ilegal do solo - Kehl, Darlene Kuki (2025)
This dissertation aims to analyze the legal liability of municipalities in the face of illegal and irregular subdivisions of urban land, in light of the Brazilian legal system. It is based on the premise that the 1988 Federal Constitution assigns to municipalities fundamental powers regarding the management, monitoring and planning of urban land use, and that they are responsible for promoting adequate territorial planning. The study is developed based on the theory of objective civil liability of the State, specifically in the modality resulting from administrative omission, as interpreted by the Superior Court of Justice. The research adopts a qualitative and dogmatic approach, based on the analysis of constitutional and infra-constitutional norms, jurisprudence, specialized doctrine and official documents. The work is structured in three chapters. The first chapter examines the main regulatory frameworks related to urban land subdivision, with emphasis on the Federal Constitution, Law No. 6,766/1979, the City Statute (Law No. 10,257/2001), and Law No. 13,465/2017. The second chapter delves deeper into the discussion on the omission of municipal public authorities and their civil liability, considering the legal, urban, and environmental impacts of negligent actions. The third chapter presents preventive and land regularization measures, with emphasis on the use of digital and geospatial technologies, the strengthening of urban planning, and the promotion of the right to the city. Finally, a critical reflection is proposed on the strategic role of municipalities in building inclusive, sustainable, and legally secure cities.